Challenges of online and face-to-face learning and its relationship with learner’s motivation among undergraduate students during the post-COVID era - Rahman, M. Mizanur; Anak Kuling, Enelson Calvin; Watumalai, Lishalinee A.; Mohamad, Qasdina Binti; Yie, Ting Sing (International Journal Of Community Medicine And Public Health, 2023)
Background: Online and face-to-face learning challenges influence students’ motivation. However, limited studies have yet been conducted to correlate students’ motivation with online and face-to-face learning challenges, especially in Malaysia. This study examined the challenges faced by learners during face-to-face and online learning and its relationship with learners’ motivation. Methods: This cross-sectional- correlation study was conducted among year-3 to year-5 undergraduate students at the Universiti Malaysia Sarawak irrespective of gender and nationality. A total of 475 students’ data were collected using a validated self-administered questionnaire. Collected data were analysed using IBM SPSS version 27.0. Pearson’s moment correlation was used to examine the association between students’ motivation and online and face-to-face learning. A p value of less than 0.05 was considered statistically significant. Results: Technological challenge was weakly positively correlated with age (p<0.05), gender (p<0.05) and amotivation (p<0.01). However, no statistically significant correlation was found with extrinsic, intrinsic motivation and CGPA (p>0.05). Among the domains of challenges, the technological challenges were strongly positively correlated with the individual (p<0.001), domestic (p<0.001), institutional (p<0.001) and community (p<0.001) challenges. This study found that extrinsic motivation was positively correlated with intrinsic motivation, but both extrinsic and intrinsic motivation were negatively correlated with amotivation. All domains of challenges were positively correlated with amotivation of students. Conclusions: Universities could organise strategies to improve the current teaching and learning methods to boost students’ extrinsic and intrinsic motivation.